1 Crore+ students have signed up on EduRev. Have you? 
∴ 5(2x + 1)(3x + 5) (2x + 1) = 5(3x+5)
26xy(x + 5) (y  4) / 13x(y  4)
Cancelling 13x(y4)
=2y(x+5)
Find and correct the errors in the following mathematical statements. 4 (x – 5) = 4x – 5
By the distributive property a(bc)=ab ac
so 4(x5)=4x20
Find and correct the errors in the following mathematical statements.
x (3x + 2) = 3x^{2} + 2
x (3x + 2)= 3x^{2}+2x (by distributive property a(b+c)=ab+ac)
10x^{2} − 18x^{3 }+ 14x^{4 }= 2x(5x− 9x^{2} + 7x^{3}) = 2x^{2}(5− 9x + 7x^{2})
x^2 + xy + 8x + 8y = x[x + y] + 8[x + y]
= (x + y)(x + 8)
We have 4y^{2 } 12y+9. comparing the equation with (ab)^{2}=a^{2}2ab+b^{2},gives us a^{2}=(2y)^{2},2ab=2*3*2y and b^{2}=(3)^{2}.Hence the answer is (2y3)^{2}.
7x²y²z²÷14xyz
=(7/14)(x²/x)(y²/y)(z²/z)
=1/2(x)(y)(z)
=1/2xyz.
Only 2y is common in both the terms
The _______ may be numbers, algebraic variables or algebraic expressions.
Factors are numbers we can multiply together to get another number. A constituent or element that brings about certain effects or results, or indicates a specific multiple, number, or quantity.
x^{4} (y+z)^{4}, applying x^{2 } y^{2}=(xa)(x+a), gives (x^{2}(y+z)^{2})(x^{2}+(y+z)^{2}). Again applying the same identity gives (x(y+z))(x+(y+z))(x^{2}+(y+z)^{2})
x^{4}(xz)^{4 }= (x^{2}(xz)^{2})(x^{2}+(xz)^{2}) = (x(xz))(x+(xz)(x^{2}+(xz)^{2}) = z(2xz)(x^{2}+(xz)^{2}(Applying a^{2 } b^{2 }= (a+b)(ab))
Divide the given polynomial by the given monominal: 8 (x^{3}y^{2}z^{2} + x^{2}y^{3}z^{2} + x^{2}y^{2}z^{3}) ÷ 4x^{2}y^{2}z^{2}
8 (x^{3}y^{2}z^{2} + x^{2}y^{3}z^{2} + x^{2}y^{2}z^{3}) ÷ 4x^{2}y^{2}z^{2}
=
Divide the given polynomial by the given monomial: (x^{3}+ 2x^{2}+ 3x) ÷ 2x
(x^{3}+2x^{2}+3x)/2x
=x(x^{2}+2x+3)/2x
=(x^{2}+2x+3)/2
Divide as directed: 52pqr (p + q) (q + r) (r + p) ÷104pq (q + r) (r + p)
Find and correct the errors in the following mathematical statements. 2x + 3y = 5xy
LHS = 2x + 3y
RHS = 5xy
LHS ≠ RHS
Correct statement would be
2x + 3y = 2x+3y
Find and correct the errors in the following mathematical statements. x + 2x + 3x = 5x
x+2x+3x=6x
Let us take 12 as common
and then the factor is 12(x+3) .
15xy  6x + 5y  2 = 3x[5y2] + 1[5y2]
= (5y  2)(3x + 1)
276 docs149 tests

Use Code STAYHOME200 and get INR 200 additional OFF

Use Coupon Code 
276 docs149 tests









